A Preliminary Experimental and Environmental Feasibility Case Study of Glass Asphalt Production in Lesvos Island, Greece. Issue 2 (December 2014) - Sinioros, Efstratios; Stamou, Periklis; Lasithiotakis, Michael; Akriotis, Dimitrios; Haralambopoulos, Dias
<x xml:space="preserve">Abstract</x> Life cycle analyses and methods for assessing performance of glass in asphalt